(untitled) (Modern education and development, 2025)
This article analyzes the role of international experiences in the development of inclusive education and the possibilities of their implementation in the conditions of Uzbekistan. The article studies the basic principles, methods and infrastructure of inclusive education using the examples of successful experiences of countries such as Finland, Italy, the USA and Japan. It also analyzes the reforms being carried out in this direction in Uzbekistan, existing problems, based on statistics and research results. The author paid special attention to such urgent issues as the training of pedagogical personnel in inclusive education, the formation of social consciousness in society, and the adaptation of infrastructure. At the end of the article, proposals are made for solving existing problems and the need to form a national model of inclusive education in Uzbekistan is justified.